Protoplast isolation and transient transformation system for Ginkgo biloba L. - Han, Xin; Rong, Hao; Feng, Yining; Xin, Yue; Luan, Xiaoyue; Zhou, Qi; Xu, Meng; Xu, Li-an (Frontiers in Plant Science, 2023)
Ginkgo biloba L. has a unique evolutionary status. Owing to its high medicinal and ornamental value, ginkgo has also recently become a research hotspot. However, the large genome and long juvenile period, as well as the lack of an effective genetic transformation system, have hindered gaining a full understanding of the comprehensive functions of ginkgo genes. At present, heterologous expression of genes in model plants is the primary method used in ginkgo-related research; however, these distant plant model relatives limit reliable interpretation of the results for direct applications in ginkgo breeding. To overcome these limitations, in this study, an efficient isolation and transient expression system for ginkgo protoplasts was established. A large number of intact and homogeneous ginkgo mesophyll protoplasts were isolated using 2% cellulase and 0.25% pectinase in 0.4 M mannitol. The activity of these protoplasts remained above 90% even after 24 h. Furthermore, when the concentration of the polyethylene glycol 4000 solution was 30%–40% (w/v), the transformation efficiency of the protoplasts reached 40%. Finally, the reliability of the system was verified using subcellular localization, transient overexpression, and protein interaction experiments with ginkgo genes, thereby providing a technical platform for the identification and analysis of ginkgo gene functions. The proposed method partially compensates for the limitations associated with the lack of a genetic transformation system and provides technical support to expand research on elucidating the functions of ginkgo genes.